Information and communication technologies and their benefits for medium and large-sized enterprises - Tichý, Ondřej (Univerzita Pardubice, 2012)
The primary research, which is brought by this paper, focuses on medium and large-sized enterprises in sectors of information and communication technologies(ICT). It investigates their attitude to the ICT that they use. Based on these ICT, the article is looking for trends set by the companies. Then, these trends could be considered as an inspiration for companies from other sectors of business. The research results have shown that the specially developed software belongs between the most often implemented ICT tools in the last seven years by the questionnaire companies. The research also showed that this ICT tool of all, which they have implemented, is the most beneficial at a tactical level. Another part of analysis, where the companies should chose benefits that arose from the implementation, pointed out that they are focused on two basic clusters of benefits. The first contains: improved teamwork and increased efficiency and effectiveness. The other cluster contains: reduced costs, improved service quality and improved integration of business functions. The research also showed thatthe surveyed companies consider the ICT only as a tool, which simplifies work.
Keywords: information and communication technologies; organizational structure; company; benefits